Rancang Bangun Sistem Digital Pemantau Suhu dan Kelembaban Ruang Server Berbasis IoT - Gios Sholid, Rolly; Yanto, H; Alhaq, Hawari; Danang Wijanarko, Satria (Riset Sinergi Indonesia (RISINDO), 2025)
Server rooms require strict temperature and humidity control to ensure the stability, reliability, and longevity of electronic devices. Excessive heat or uncontrolled moisture may lead to hardware degradation, reduced system performance, and potential service interruptions. To address these challenges, this study presents the design and implementation of an IoT-based digital monitoring system that integrates an ESP32 microcontroller with a DHT22 temperature–humidity sensor. The collected data are transmitted via Wi-Fi to the ThingSpeak cloud platform, where they are stored, processed, and visualized in real time. The research method covers hardware prototyping, firmware programming, and a 24-hour continuous simulation to evaluate system performance. Experimental results indicate that the monitoring system successfully records temperature variations within the range of 22–30°C and relative humidity levels between 45–65%. When validated against a calibrated reference device, the system achieves an average measurement error of 0.6°C for temperature and 2.1% RH for humidity, which demonstrates adequate precision for server room applications. In terms of communication performance, the data upload to ThingSpeak shows an average latency of 1.2 seconds with a transmission success rate of 99%, ensuring reliable remote accessibility. Furthermore, the system is equipped with configurable alarm thresholds that provide early warnings whenever the environmental conditions exceed safe operating limits. Overall, the proposed IoT-based monitoring design proves to be a feasible, scalable, and low-cost solution for server room environments. It not only supports preventive maintenance by enabling timely detection of anomalies but also offers a practical model for extending digital monitoring to other critical facilities where environmental stability is essential.